Integrated coastal management and town planning in Malaysia: concept and practice - Asmawi, M. Zainora (VDM publishing, 2010)
In Malaysia, research on coastal and estuarine areas is still new and fragmented between various disciplines, like coastal geomorphology, coastal engineering and marine biology, which tend to be institutionally or individually oriented. A systematic study of coastal and marine natural resources in the context of town planning (TP) is very limited. So, the literature study did not explore the relationship between integrated coastal management (ICM) and TP in Malaysia, though general elements of TP were mentioned. There is inadequate literature involving the scope of local ICM by Basiron (1998, 2000), Mokhtar and Aziz (2003) and Pedersen, Beck, Johansen and Jensen (2005).